2008
DOI: 10.1017/s0007485308006160
|View full text |Cite
|
Sign up to set email alerts
|

Hearing in tsetse flies? Morphology and mechanics of a putative auditory organ

Abstract: Tympanal hearing organs are widely used by insects to detect sound pressure. Such ears are relatively uncommon in the order Diptera, having only been reported in two families thus far. This study describes the general anatomical organization and experimentally examines the mechanical resonant properties of an unusual membranous structure situated on the ventral prothorax of the tsetse fly, Glossina morsitans (Diptera: Glossinidae). Anatomically, the prosternal membrane is backed by an air filled chamber and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This is not surprising as Gr68a also participates in sound reception [ 66 ]. Absence of Gr68a in tsetse could imply that tsetse flies rely on a different receptor other than Gr68a for sound reception, or that the insects rely entirely on their tympanal organ for this function [ 79 ]. Additionally, absence of Gr68a has been reported to reduce male-male courtship in Drosophila and perhaps may play the same role in tsetse flies [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as Gr68a also participates in sound reception [ 66 ]. Absence of Gr68a in tsetse could imply that tsetse flies rely on a different receptor other than Gr68a for sound reception, or that the insects rely entirely on their tympanal organ for this function [ 79 ]. Additionally, absence of Gr68a has been reported to reduce male-male courtship in Drosophila and perhaps may play the same role in tsetse flies [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known importance of the antennal flagellum for detecting post-feeding sound ( Popham et al 1978 ), more recently it has been found that the prothorax membrane could possibly be a tympanal hearing organ ( Tuck et al 2009 ). Interestingly, these two types of receptors usually have different properties, with tympani having greater sensitivity to long-range sounds and higher frequencies ( Yack 2004 ).…”
mentioning
confidence: 99%
“…The ear of E. auditrix is located at the ventral prothorax directly below the cervical sclerites and the two tympanal membranes face forward ( Lakes-Harlan et al 1999 ), as it is the case for all known tympanate Diptera ( Lakes-Harlan and Heller 1992 , Edgecomb et al 1995 , Lakes-Harlan et al 2007 , Tuck et al 2009 ). The tympanal membranes have an average area of 0.32 mm² (mean of left and right tympana) and are within the range of other flies, like O. ochracea (0.29 mm 2 , Robert et al 1994 or G. morsitans (0.53 mm 2 , Tuck et al 2009 ). In E. auditrix , we found a positive correlation of the size of the ear to body size, but it is unknown whether the size influences physiological properties of the auditory system.…”
Section: Discussionmentioning
confidence: 99%
“…At both membranes, a scolopidial sense organ inserts with about 35 uniformly sized mononematic scolopidia, each with one sensory neuron ( Lakes-Harlan et al 1999 ). The tympanal ear of Emblemasomatini and Orminii represent an example of convergent evolution from a precursor structure, the vibration-sensitive chordotonal organ in nonhearing flies ( Edgecomb et al 1995 , Lakes-Harlan et al 1999 ) and possibly an advancement of the membranous prosternal organ in the tsetse fly Glossina morsitans ( Tuck et al 2009 ). Physiologically, the hearing system of E. auditrix seems to be adapted to its host calling song (CS; Lakes-Harlan and Lehmann 2015 ), but anatomical and physiological data at large are missing.…”
mentioning
confidence: 99%